2006
DOI: 10.1111/j.1600-0668.2006.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

The modern office environment desiccates the eyes?

Abstract: Eye irritation is a common complaint in the office environment. The purpose of this overview is to merge knowledge within indoor air science, ophthalmology, and occupational health to promote understanding eye irritation symptomatology, the cause of which is still partly unknown. High periocular relative humidity appears to protect the pre-corneal tear film against desiccation and sensory irritating pollutants and reduces the development of eye irritation symptoms. This is particularly relevant for intensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 66 publications
1
62
0
4
Order By: Relevance
“…Emission of the volatile organic compounds (VOCs) from the synthetic materials used in homes and offices together with other micro environmental variables such as temperature, humidity, lighting and airborne substances can also contribute to EDED. They can cause ocular symptoms, tear film instability, and alterations in ocular surface characteristics of EDED (40,62,(71)(72)(73)(74) . In 1992, Norn described that "sick building" workers have "pollution keratoconjunctivitis" with decline in BUT values and epithelial alterations detected by lissamine green staining (31) .…”
Section: Epidemiology Of Dry Eye Related To Environmental Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Emission of the volatile organic compounds (VOCs) from the synthetic materials used in homes and offices together with other micro environmental variables such as temperature, humidity, lighting and airborne substances can also contribute to EDED. They can cause ocular symptoms, tear film instability, and alterations in ocular surface characteristics of EDED (40,62,(71)(72)(73)(74) . In 1992, Norn described that "sick building" workers have "pollution keratoconjunctivitis" with decline in BUT values and epithelial alterations detected by lissamine green staining (31) .…”
Section: Epidemiology Of Dry Eye Related To Environmental Factorsmentioning
confidence: 99%
“…Based on the studies performed using questionnaires, it ranges from 5%-40% (62,75) . This large range may be due to the design of questionnaire, types of reported symptoms, inclusion of confounding variables that include contact lens wear, medications, and differences in recall periods.…”
Section: Epidemiology Of Dry Eye Related To Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological and clinical studies suggest that 40% RH is a favourable condition for the precorneal tear film (Wolkoff 2008). Some studies have shown a correlation between increasing RH and more stable pre-corneal tear film measured by break-up time (Brasche 2005;Norbäck 2006;Wolkoff 2006). In a study conducted by Wyon 2006, the blink frequency was significantly lower at 35% than at 5% RH.…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…As noted, the trigeminal nerve also innervates the eyes, so vapors reaching the ocular mucosa can give rise to eye irritation, a key symptom invariably mentioned in studies of indoor air pollution (Korpi et al, 2009;Wolkoff et al, 2006;Wolkoff et al, 2003). Eye irritation thresholds (EITs) were measured in normosmics for homologous nalcohols, acetate esters, 2-ketones, n-alkylbenzenes, for various terpenes, and for cumene, using a methodology analogous to that described above for NPTs, including vapor quantification via gas chromatography (Cometto-Muñiz and Cain, 1991;Cometto-Muñiz et al, 1998b).…”
Section: Insert Figure 2 About Herementioning
confidence: 99%